Analysis and verification of the circRNA regulatory network RNO_CIRCpedia_ 4214/RNO-miR-667-5p/Msr1 axis as a potential ceRNA promoting macrophage M2-like polarization in spinal cord injury - Jian Cao; Chongzhi Pan; Jian Zhang; Qi Chen; Tao Li; Dingwen He; Xigao Cheng (BMC Genomics, 2023)
Abstract Background CircRNAs are involved in the pathogenesis of several central nervous system diseases. However, their functions and mechanisms in spinal cord injury (SCI) are still unclear. Therefore, the purpose of this study was to evaluate circRNA and mRNA expression profiles in the pathological setting of SCI and to predict the potential function of circRNA through bioinformatics. Methods A microarray-based approach was used for the simultaneous measurement of circRNAs and mRNAs, together with qPCR, fluorescence in situ hybridization, western immunoblotting, and dual-luciferase reporter assays to investigate the associated regulatory mechanisms in a rat SCI model. Results SCI was found to be associated with the differential expression of 414 and 5337 circRNAs and mRNAs, respectively. Pathway enrichment analyses were used to predict the primary function of these circRNAs and mRNAs. GSEA analysis showed that differentially expressed mRNAs were primarily associated with inflammatory immune response activity. Further screening of these inflammation-associated genes was used to construct and analyze a competing endogenous RNA network. RNO_CIRCpedia_4214 was knocked down in vitro, resulting in reduced expression of Msr1, while the expression of RNO-miR-667-5p and Arg1 was increased. Dual-luciferase assays demonstrated that RNO_CIRCpedia_4214 bound to RNO-miR-667-5p. The RNO_CIRCpedia_4214/RNO-miR-667-5p/Msr1 axis may be a potential ceRNA that promotes macrophage M2-like polarization in SCI. Conclusion Overall, these results highlighted the critical role that circRNAs may play in the pathophysiology of SCI and the discovery of a potential ceRNA mechanism based on novel circRNAs that regulates macrophage polarization, providing new targets for the treatment of SCI.